CRISPR-Cas9 as a Powerful Tool for Efficient Creation of Oncolytic Viruses - Ming Yuan; Eika Webb; Nicholas Robert Lemoine; Yaohe Wang (Viruses, 2016)
The development of oncolytic viruses has led to an emerging new class of cancer therapeutics. Although the safety profile has been encouraging, the transition of oncolytic viruses to the clinical setting has been a slow process due to modifications. Therefore, a new generation of more potent oncolytic viruses needs to be exploited, following our better understanding of the complex interactions between the tumor, its microenvironment, the virus, and the host immune response. The conventional method for creation of tumor-targeted oncolytic viruses is based on homologous recombination. However, the creation of new mutant oncolytic viruses with large genomes remains a challenge due to the multi-step process and low efficiency of homologous recombination. The CRISPR-associated endonuclease Cas9 has hugely advanced the potential to edit the genomes of various organisms due to the ability of Cas9 to target a specific genomic site by a single guide RNA. In this review, we discuss the CRISPR-Cas9 system as an efficient viral editing method for the creation of new oncolytic viruses, as well as its potential future applications in the development of oncolytic viruses. Further, this review discusses the potential of off-target effects as well as CRISPR-Cas9 as a tool for basic research into viral biology.